ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI MINAT BELI SOMETHINC DI KOTA TANGERANG SELATAN (STUDI PADA PLATFORM TIKTOK SHOP) - Rina Inggrid Anatasya; I Made Bayu Dirgantara; Rista Nurdianasari (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT The presence of the Internet in the community has facilitated various aspects and means of people's lives, such as communication facilities, learning facilities, and sources of information using various media. One of them is by using social media. Even during this pandemic, almost everyone, including the people of Indonesia, has made the Internet their primary need. The research aims to analyze what factors can increase Purchase Intention for skincare products Somethinc by TikTok users in South Tangerang City. The research sample consisted of 125 sample determinations, namely nonprobability sampling and purposive sampling where the researchers gave the limitations that would be used as samples were young consumers in South Tangerang City aged 16 to 30 years who had purchased skincare Something. The analysis tool uses the AMOS 22.00 SEM method (Structural Equation Modeling). The results of the study show that there is a significant effect of Electronic Word of Mouth on Brand Image with a p-value of ***, which means that it is close to Zero <0.05 (H1 is accepted). Electronic Word of Mouth on Purchase Intention with a p-value of 0.035 (H2 accepted). There is a significant influence of Brand Image on Purchase Intention with a p-value of 0.007 (H3 accepted). The determination value is known as the effective contribution of Electronic Word of Mouth and Brand Image to Purchase Intention of 0.178 or 17.8%